24-h urinary free cortisol from mid-pregnancy to 3-months postpartum: Gender and parity differences and effects - Conde, Ana (2015)
Background: Pregnancy and postpartum have been associated to several physiological changes;however, empirical evidence was almost exclusively obtained in primiparous women and few studies focus on hormonal changes in men and second-time parents. The main aim of this study is to examine 24-h urinary free cortisol from mid-pregnancy to 3-months postpartum, comparing women/men and ﬁrst/second-time parents. Methods: Twenty-six women and 22 men (N = 48) were recruited from an antenatal obstetric unit in Porto, Portugal. 24-h urinary free cortisol was measured at the 2nd and 3rd trimester and at 3-months postpartum. Repeated measures analyses of variance were conducted, in order to analyze 24-h urinary free cortisol patterns of change over this period. Gender and parity were included in the analyses as potential modiﬁers, in order to compare women and men, and ﬁrst-and second-time parents. Results: An increase from the 2nd to the 3rd trimester (p = .006) and a decrease from the 3rd trimester to 3-months postpartum (p = .005) were reported in all parents’ 24-h urinary free cortisol. The interaction effects for Time * Gender (p = .03) and Time * Parity (p = .02) were found. Women and ﬁrst-time parents revealed higher levels, while men and second-time parents showed lower 24-h urinary free cortisol levels at the 2nd trimester than at 3-months postpartum. Conclusions: Findings appear to clarify the direction, as well as, the timing, gender and parity extension of 24-h urinary free cortisol changes from mid-pregnancy to 3-months postpartum. The same pattern of change in all parents’ 24-h urinary free cortisol from mid-pregnancy to 3- months postpartum is consistent with the proposed role of hormones in preparation to parenting.